An Analysis of Questioning Strategies in Secondary Mathematics Classroom - Bohara, Chhabi Lal (Journal of Musikot Campus, 2024)
This article aimed to assess the current questioning practices and explore their impact in secondary-level mathematics classrooms in Lekhbeshi Municipality, Surkhet district. The researcher adopted a mixed-methods research design, selecting eighty students randomly from four schools for the quantitative component and four teachers along with four students for the qualitative component. Data were collected through questionnaires, interviews, and observations. Statistical tools were employed to analyze quantitative data, while triangulation was used for qualitative themes. The study revealed that poor student performance was linked to inadequate implementation of techniques such as APPLE, DEAL, CLAPS, and the 5W method. Conversely, effective questioning strategies correlated with better student outcomes in mathematics. The findings underscore the importance of teachers mastering the art of student questioning, as it is crucial for fostering curiosity and enhancing learning in mathematics. Inadequate questioning practices can lead to classroom disruption and unproductive results. The study recommends further comparative research on questioning practices in mathematics classrooms and their effects on student achievement in Nepalese schools.